2018
DOI: 10.1136/emermed-2017-207435
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of NEXUS II head injury decision rule in children: a prospective PREDICT cohort study

Abstract: NEXUS II had high sensitivity, similar to the derivation study. However, approximately half of unimaged patients were positive for NEXUS II risk criteria; this may result in an increased CT rate in a setting with high clinician accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…Therefore, solely using risk-stratification models in the acute care setting seems questionable. This statement is in concordance with prior literature stating that prediction of patient outcome by decision rules is inferior compared with clinical gestalt 16–19…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, solely using risk-stratification models in the acute care setting seems questionable. This statement is in concordance with prior literature stating that prediction of patient outcome by decision rules is inferior compared with clinical gestalt 16–19…”
Section: Discussionsupporting
confidence: 91%
“…Strict adherence to National Early Warning Score (NEWS) by general practitioners was shown to have the potential to increase (unneeded) hospital admissions 15. Classification of disease severity based on developed decision rules is inferior compared with clinical performance 16–20…”
Section: Introductionmentioning
confidence: 99%
“…97%-os érzékenységet mutatott a klinikailag jelentős agysérülések kiemelésére a tompa fejsérülést szenvedett betegek körében, valamint 95,1%-os szenzitivitással és 41,4%-os specificitással bírt az idegsebészeti beavatkozást igénylő elváltozások azonosításában. A szükséges CT-vizsgálatok számát jobban csökkentette, mint a másik két rendszer (2. táblázat) [13,14]. Vizsgálatunkból megállapítható, hogy az ellátásra, obszervációra szoruló koponyasérültek betegcsoportját a CCHR-kritériumok segítségével biztonsággal azonosítani lehet mindamellett, hogy ez a módszer az elvégzett CT-vizsgálatok biológiai, illetve finanszírozási terhelését is nagymértékben csökkenti.…”
Section: Közepes Kockázati Tényezők (Látható Agysérülés Ct-felvételeken)unclassified
“…The sensitivities of the CATCH and CHALICE criteria in this study were 95% and 92%, respectively, and the CATCH algorithm resulted in a greater number of CT scans performed. A large prospective validation study of the NEXUS II criteria in children demonstrated 95% sensitivity for intracranial injury but resulted in a relatively high rate of CTs [13]. Additional smaller validation trials in the United States and abroad have also determined the PECARN criteria for very low risk criteria to be 100% sensitive [14][15][16][17].…”
Section: Summary Of Literature Review Introduction/backgroundmentioning
confidence: 99%